Pengaruh Entrepreneurship Education terhadap Entrepreneurial Intentions pada Mahasiswa Universitas Syiah Kuala - Jannah, Auliatil; Nurlina, Nurlina; Yurnalis, Yurnalis (Manajemen Inovasi Bisnis dan Strategi, 2023)
Abstrak:Penelitian ini bertujuan untuk mengukur pengaruhEntrepreneurship EducationterhadapEntrepreneurial IntentionsdenganSelf EfficacydanLearning Orientationsebagai variabel mediasi pada mahasiswa Universitas Syiah Kuala.Sampel yang digunakan dalam penelitian ini adalah Mahasiswa FEB USK yang berjumlah 100 responden.Peralatan pengumpulan data yang digunakan pada penelitian ini adalah kuesioner.Teknik pengambilan sampel yang digunakan adalahCluster Random Sampling, dan Uji Sobel digunakan sebagai metode analisis untuk mengetahui pengaruh dari semua variabel-variabel yang terlibat.Berdasarkan hasil analisis Uji Sobel, mengindikasikan bahwaEntrepreneurship Educationberpengaruh terhadapEntrepreneurial Intentions, Entrepreneurship Educationberpengaruh terhadapSelf Efficacy, Entrepreneurship Educationberpengaruh terhadapLearning Orientation, Self Efficacyberpengaruh terhadapEntrepreneurial Intentions, Learning Orientationberpengaruh terhadapEntrepreneurial Intentions, Self Efficacymemediasi secara parsialpengaruh Entrepreneurship EducationterhadapEntrepreneurial Intentions, Learning Orientationmemediasi secara parsial pengaruhEntrepreneurship EducationterhadapEntrepreneurial Intentions.Abstract:This study aims to measure the effect of Entrepreneurship Education on Entrepreneurial Intentions with Self Efficacy and Learning Orientation as mediating variables in students of Syiah Kuala University. The sample used in this study was FEB USK students, totaling 100 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used was Cluster Random Sampling, and the Sobel test was used as an analytical method to determine the effect of all the variables involved. Based on the results of the Sobel Test analysis, it indicates that Entrepreneurship Education influences Entrepreneurial Intentions, Entrepreneurship Education influences Self Efficacy, Entrepreneurship Education influences Learning Orientation, Self Efficacy influences Entrepreneurial Intentions, Learning Orientation influences Entrepreneurial Intentions, Self Efficacy partially mediates the influence of Entrepreneurship Education on Entrepreneurial Intentions, Learning Orientation partially mediates the influence of Entrepreneurship Education on Entrepreneurial Intentions.Keywords:Entrepreneurship Education, Entrepreneurial Intentions, Self Efficacy, Learning Orientation